‘Mental heAlth and well-being in rUgby pLayers’ (MAUL) study: an online survey of diverse cohorts of rugby union players internationally - Jon Patricios; Paul Kelly; Simon Kemp; Debbie Palmer; Karim Khan; Caithriona Yeomans; Kathryn Dane; Steffan Griffin; Samantha Fawkner; Heather Lewis; Kearnan Myall; Rebecca Syed Sheriff; et al. (BMJ Open Sport & Exercise Medicine)
Introduction Mental health and well-being is a relatively under-researched area in rugby, especially outside the elite men’s game. Evidence suggests that physical activity and sports benefit mental health and well-being, and rugby provides health-enhancing moderate-to-vigorous physical activity.Objective This cross-sectional study used an online approach and engaged national rugby governing bodies to understand adult rugby players’ mental health and well-being and increase the diversity of the current evidence base.Results 500 rugby players completed an online survey. 44% of participants identified as female, and 55% as male. The UK (67%), Ireland (15%) and South Africa (12%) were the countries with the highest representation. 71% of participants were amateur players, with elite players making up 20% of the population. 87% of players participated in contact forms of the game, with 9% predominantly playing non-contact rugby. Over 50% of participants reported that rugby impacted ‘extremely’ positively on both their mental health and well-being. Based on the Kessler psychological distress scale (K10), 57.8% of all respondents belonged to the ‘psychologically well’ group. Males were more likely to belong to this group than females (p=0.01). Non-contact and amateur players had lower scores of psychological distress than contact and professional players (p=0.001 and p=0.006), respectively. Non-contact players had higher well-being (Short Warwick-Edinburgh Mental Well-being Scale) scores than contact players (p<0.001).Conclusion This study provides new insights into the mental health and well-being of a diverse group of rugby players.